Killing me softly examination of the court's emasculation of it's own doctrines of primary jurisdiction and exhaustion of administrative remedies (Philippine Law Journal, 2021)
Jurisprudence shows numerous exceptions to the court-created doctrines of primary jurisdiction and exhaustion of administrative remedies. Thirty-four (34) exceptions are found, the latest one being decided in 2019. This Note first revisits the history and developments of these doctrines and examines the judicial trend in this area of administrative law. It then submits that with the current number of immunities, the Court is traversing a slippery slope of instability, implicitly negating itself, and making its commitment to the trend merely illusory. Various institutional and legal effects of repeatedly adding exceptions to these doctrines are then examined, which include: sacrificing the benefits drawn from the doctrines; risking a lack of clear judicial philosophy; weakening the value of case precedents; adding burdens to the courts' decision-making process; tending towards the absence of predictability; promoting judicial activism; undermining agencies' authority; and preventing agencies' arbitrary actions. Keeping in mind the doctrine's underlying purpose, this Note finally frames a test for courts to better address the issues of pamary junsdiction and exhaustion. The analysis intends to reach simple, clear, consistent, and predictable results.